Reimagining "One Nation, One Music" - Das, Iman; Mutthuswamy, Lalitha; Mutthuswamy, Nandini (Gurugram Shubhi Publications, 2022)
India has never been a land of mono-culture. The subcontinent, on the contrary, has always been a melting pot of languages, religions, belief systems, social hierarchies and myriads of fine arts, performing arts and applied arts and crafts. In music alone, there have been multiple strands: devotional, ethnic, folk and popular varieties, among others. In Indian classical music, however, there has been a remarkably unified approach since the Vedic times up to the middle ages: beginning with Ssam Gaans / Gadharva Gaans, various forms of Pabandhas, and then a variety of Dhruvapadas / Dhrupads until the 13th century. The context for (3z(Bre-imagining(3y (BIndian classical music is because, (as noted by the great musicologist, Thakur Jaidev Singh), Raja Man Singh (1486-1516) of Gwalior gave a new orientation to Salaga-Suda-Prabandha, $1 (Bwith the assistance of Nayaka Bakshu and Lohang and Pandviya, who had come from the South. Due to Islamaisation, many Sanskrit musical treatises were not fully followed. Especially, the singing style got relaxed into giving vent to a lot of improvisations (as, for instance, in Alaap in Bada Kayal and Chhota Khayal) and Bol Banao, Bhao Batao, etc., in Thumri) in the Muslim period in the North; while Kritis and Keertans by the renowned (3z(BMusic Trinity(3y (B(Thyagaraja, Shyama Sastry, Mthuswamy Dikshiter) and Keertanas by Annamacharya, both in Tamil and Telugu, remained fixed in musical memory of the masses over time. Thus, gradually, Indian classical music bifurcated into Hindustani and Carnatic systems, as noted by Sharanga Deva in his Sangeet Ratnakar in 13th-15th century. Again, in a nutshell, two major differences between the two systems remained in time, namely, first, preponderance of only devotional compositions in the Carnatic system against total secularity in the Hindustani compositions and, second, minor role assigned to improvisational Nirbalas in Carnatic music against a very great dominance of improvisations in Hindustani music.s
Keywords: Music for Eternity -- Music Under One Sky